Effect of Variability in Sources of Low-Density Polyethylene on the Intermediate Temperature Fatigue Performance of Modified Bitumen - Singh A.; Gupta A. (My University, 2025)
The current study aims to evaluate the fatigue performance of bitumen modified with low-density polyethylene (LDPE) from various sources. To achieve this, viscosity-graded (VG 30) base bitumen was modified with 3% waste plastic by volume of bitumen. The experimental program included a linear amplitude sweep test (LAS) at 15 ℃. The modified bitumen exhibited higher stiffness and improved fatigue resistance. The fatigue performance of bitumen at intermediate temperatures was significantly affected by the variation of sources of plastics. Among the different sources of LDPE, bitumen modified with LDPE from source 4 exhibited the highest fatigue life. While previous studies have attributed the improvement in fatigue life to the higher degree of crystallinity of polymers, this study observed that the melt flow index (MFI) also plays a crucial role in addition to the degree of crystallinity. However, it remains unknown which parameter is more dominant. Furthermore, bitumen modified with plastics having a higher degree of crystallinity presented lesser ductile failure. Overall, the modified bitumen demonstrated better performance at intermediate service temperatures. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.